2023
DOI: 10.3389/fbioe.2023.1144624
|View full text |Cite
|
Sign up to set email alerts
|

Effective-mononuclear cell (E-MNC) therapy alleviates salivary gland damage by suppressing lymphocyte infiltration in Sjögren-like disease

Abstract: Introduction: Sjögren syndrome (SS) is an autoimmune disease characterized by salivary gland (SG) destruction leading to loss of secretory function. A hallmark of the disease is the presence of focal lymphocyte infiltration in SGs, which is predominantly composed of T cells. Currently, there are no effective therapies for SS. Recently, we demonstrated that a newly developed therapy using effective-mononuclear cells (E-MNCs) improved the function of radiation-injured SGs due to anti-inflammatory and regenerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…However, these results clearly demonstrated that allogeneic UC‐MSC infusion is a promising and effective treatment for SS. After confirming the safety of E‐MNCs in patients with radiogenic xerostomia and therapeutic effects on NOD mice with SS‐like disease (Hasegawa et al, 2023), we will be taking part in a sponsor‐initiated clinical trial of E‐MNC treatment for SS patients. This clinical trial being conducted by CellAxia Inc. (Tokyo, Japan) is a randomized, multi‐center, phase II, double‐blind, placebo‐controlled trial.…”
Section: Clinical Studies On Patients With Ssmentioning
confidence: 83%
See 2 more Smart Citations
“…However, these results clearly demonstrated that allogeneic UC‐MSC infusion is a promising and effective treatment for SS. After confirming the safety of E‐MNCs in patients with radiogenic xerostomia and therapeutic effects on NOD mice with SS‐like disease (Hasegawa et al, 2023), we will be taking part in a sponsor‐initiated clinical trial of E‐MNC treatment for SS patients. This clinical trial being conducted by CellAxia Inc. (Tokyo, Japan) is a randomized, multi‐center, phase II, double‐blind, placebo‐controlled trial.…”
Section: Clinical Studies On Patients With Ssmentioning
confidence: 83%
“…However, these results clearly demonstrated that allogeneic UC-MSC infusion is a promising and effective treatment for SS. After confirming the safety of E-MNCs in patients with radiogenic xerostomia and therapeutic effects on NOD mice with SS-like disease(Hasegawa et al, 2023), we will be taking part in a sponsor-initiated clinical trial of E-MNC treatment for SS patients.This clinical trial being conducted by CellAxia Inc. (Tokyo, Japan) is a randomized, multi-center, phase II, double-blind, placebo-controlled trial. This phase II clinical trial will hopefully provide a strong foundation for the clinical use of E-MNC therapy, which could develop into an alternative treatment for xerostomia caused by SS.6 | FUTURE PROS PEC TS OF CELL-BA S ED THER APIE S FOR TRE ATING SG HYP OFUN C TIONAs mentioned above, cell-based therapy using MSCs is considered safe and exhibits therapeutic effects against SG dysfunction in| et alpatients undergoing radiation therapy for head and neck cancer and patients with SS.…”
mentioning
confidence: 95%
See 1 more Smart Citation